Physical activity & behavioral medicine - Sallis, James F.; Owen, Neville; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 1999)
Adopting a behavioural epidemiology framework, the authors offer an examination of what is known about physical health and activity.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Medicine and psychology; Physical fitness -- Physiological aspects; Physical fitness -- Psychological aspects; Health; Electronic books